2021
DOI: 10.14366/usg.21014
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of ultrasonography and shear wave sonoelastography in Sjögren syndrome with salivary gland involvement

Abstract: The purpose of this study was to investigate the effectiveness of major salivary gland ultrasonography (MSGUS) by using new grading system and shear wave elastography (SWE) in evaluating the major salivary glands of patients with Sjögren's Syndrome (SjS). Material and Methods:This prospective designed cross sectional study included 49 SjS patients and 49 healthy controls. Major salivary glands were examined by gray scale ultrasonography and SWE. A new grading system for salivary glands was made by using MSGUS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 30 publications
1
22
2
Order By: Relevance
“…In our study, we found by elastography stiffer tissue in both parotid and submandibular glands by pixel analysis, the finding was associated significantly with minor glands and low unstimulated whole saliva flow rate; it can translate as chronic damage or its consequences; differing to what Zhang et al found in their study in which the parotid was the most involved gland ( 20 , 21 ).…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…In our study, we found by elastography stiffer tissue in both parotid and submandibular glands by pixel analysis, the finding was associated significantly with minor glands and low unstimulated whole saliva flow rate; it can translate as chronic damage or its consequences; differing to what Zhang et al found in their study in which the parotid was the most involved gland ( 20 , 21 ).…”
Section: Discussioncontrasting
confidence: 95%
“…Additionally, it accompanies the initial inflammatory and fibrotic process, which is not evaluated adequately since parotid or submandibular biopsies are not recommended ( 22 ). However, fatty tissue is an inflammatory tissue, so detecting initial changes with elastography, especially with pixel analysis leads to early diagnosis of inflammation or fibrosis and fatty infiltrate in the gland; as has been done in other studies in which elasticity index has been used ( 13 , 20 ), but not this novel pixel analysis technique. Our finding suggests a path, possibly related to fatty tissue inflammation, to evaluate early damage, as Skarstein et al ( 22 ) previously showed.…”
Section: Discussionmentioning
confidence: 99%
“…22 Some studies have shown that elastography combined with SGUS may be useful for the diagnosis of pSS. [109][110][111] pSS is associated with inflammation and fibrosis. Thus, patients with pSS can present with increased SG stiffness, mainly because of structural changes of glandular parenchima.…”
Section: Key Pointsmentioning
confidence: 99%
“…[113][114][115] Thus far, elastography studies of SGs of pSS patients have been conducted in small cohorts of patients. [111][112][113][114][115] Moreover, there are substantial differences among the three aforementioned modalities to obtain elastography. 108 Therefore, it is not possible to make a final statement about the usefulness of elastography in diagnosing and monitoring pSS.…”
Section: Key Pointsmentioning
confidence: 99%
“…Salivary gland US has gained increased attention over the last decade, and some studies have demonstrated that the addition of US increases the performance of the ACR‐EULAR criteria 5,9,10 . The sensitivity and specificity of gray‐scale US studies assessing the salivary gland parenchyma in the literature are 46%–92% and 65%–98%, respectively, with substantial variation between studies 11–14 . However, in the majority of these studies, US is dependent on the user and subjective.…”
Section: Introductionmentioning
confidence: 99%